ECONOMIC FACTORS THAT INFLUENCE THE PRODUCTIVITY OF THE GEN Z FARMING COMMUNITY IN TASIKMALAYA CITY: DOES THE URBAN FARMING CONCEPT IDEAL? - Prasetyo, Rizki Maulana; Nurhuda, Habib; Alfian, Slamet; Alvan, Eri Nur (Jurnal Bina Bangsa Ekonomika, 2025)
The study aims to evaluate the influence of economic factors such as income, consumption of agricultural products, investment, and the quality of human resources on the productivity of the Generation Z farming community in Tasikmalaya City, as well as assessing whether the urban farming concept is an ideal method for increasing their productivity. Using quantitative methods and a descriptive approach, data was collected through questionnaires distributed to 60 members of the Gen Z farming community in Tasikmalaya City, and multiple linear regression analysis was used to assess the relationship between independent and dependent variables. The research results show that income has a significant positive influence on agricultural productivity. Consumption of agricultural products also shows a significant positive relationship. Consistent with researchers where increased income encourages the expansion of crop varieties and innovations in planting techniques. Agricultural product consumption also shows a significant positive relationship, supporting the increasing agricultural product consumption drives land expansion and new seed planting. Investment has a significant positive impact on productivity, as increased investment enhances production activities. Furthermore, HRQ significantly positively impacts the productivity of Gen Z farmers, suggesting that skilled and knowledgeable farmers can better implement urban farming practices. Investment has a significant positive effect on agricultural productivity. Hypothesis testing shows that all independent variables have a significant relationship with the dependent variable, with a probability value of t < 0.05 and a probability value of f < 0.05. The classical assumption test shows that this regression model is valid and reliable, with normality, autocorrelation, heteroscedasticity and multicollinearity test results in accordance with accepted standards. Based on these results, it can be concluded that income, consumption of agricultural products, investment and quality of human resources contribute significantly to the productivity of Gen Z farmers in Tasikmalaya City. This research also confirms that the urban farming concept is an effective method for increasing the efficiency and quality of production in cities, providing important implications for sustainable agricultural policies and practices. Strategies for increasing income, optimizing consumption of agricultural products, increasing investment and developing the quality of human resources are key factors in increasing the productivity of the agricultural sector in the digital era. Thus, urban farming can be implemented effectively by the Gen Z farming community in Tasikmalaya City